Biomass resin composition

A biomass resin composition combining biomass resin and hydroxyalkyl cellulose addresses the strength and heat resistance issues of biomass materials by enhancing transparency and strength while maintaining low specific gravity through solvent-assisted mixing and kneading processes.

JP7604107B2Active Publication Date: 2024-12-23OSAKA GAS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020060037
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-30
Publication Date
2024-12-23
Estimated Expiration
2040-03-30

AI Technical Summary

Technical Problem

Biomass materials and biodegradable plastics often suffer from inferior strength and heat resistance, and adding non-biomass fillers like glass fibers increases specific gravity, compromising their characteristics.

Method used

A biomass resin composition containing a biomass resin and a hydroxyalkyl cellulose compound, which enhances transparency, strength, and heat resistance without the need for non-biomass fillers, using methods that include kneading and mixing in the presence of a polar solvent to prevent aggregation.

Benefits of technology

The composition achieves improved transparency, strength, and heat resistance while maintaining a low specific gravity, with the hydroxyalkyl cellulose compound promoting affinity with hydrophobic polymers and preventing aggregation of cellulose nanofibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604107000005
    Figure 0007604107000005
  • Figure 0007604107000006
    Figure 0007604107000006
  • Figure 0007604107000007
    Figure 0007604107000007
Patent Text Reader

Abstract

To provide a biomass resin composition having excellent transparency, strength and heat resistance without addition of non-biomass filler.SOLUTION: A biomass resin composition contains a biomass resin and a hydroxyalkyl(alkyl)cellulose compound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a biomass resin composition. [Background technology]

[0002] Biomass resources are attracting attention from the viewpoints of reducing energy consumption, utilization of fossil resources, and carbon dioxide emissions (low carbonization), as well as weight reduction. In addition, biodegradable materials are also attracting attention due to the issue of microplastics (for example, see Non-Patent Document 1).

[0003] However, many biomass and biodegradable materials are inferior in strength and heat resistance. For example, even polylactic acid, a typical example of biomass resin that is synthesized as a plastic by polymerizing lactic acid, is inferior in strength to ABS resin, a non-biomass resin, and is also a plastic with low heat resistance, so it is assumed that it will be used together with a reinforcing agent such as glass fiber (see, for example, Patent Document 1 and Non-Patent Document 2).

[0004] Regarding biomass plastics, which have poor strength and heat resistance, attempts have been made to reinforce them by adding fillers; however, when glass fibers are added as in Patent Document 1, the specific gravity becomes high and the properties of the biomass material cannot be utilized.

[0005] For this reason, it is conceivable to use natural materials as fillers to increase the biomass ratio and reduce weight. In order to maintain strength, it is common to pre-treat the biomass and add non-biomass additives, but from the standpoint of biodegradability and biogas purification, it is considered preferable for the components to be 100% biomass materials by mass. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2014-198820 A [Non-patent literature]

[0007] [Non-Patent Document 1] Issues and future prospects for biodegradable plastics; Mitsubishi Research Institute Technical Report (2019) [Non-Patent Document 2] PIONEER R&D Vol.16 No.1,33-39(2006) Summary of the Invention [Problem to be solved by the invention]

[0008] Cellulose is the main component of plant cell walls and plant fibers, and is a natural polymer in which many β-glucose molecules are polymerized in a linear chain through glycosidic bonds, so it has a small environmental impact. Cellulose fibers made of this cellulose have a structure in which single cellulose nanofibers, which are the basic units in the cell wall and have a width of 10 to 20 nm, are bundled together, and these are further bundled together to a thickness of several tens of μm. Since the raw material pulp and cellulose powder contain hemicellulose and, in some cases, lignin, cellulose nanofibers often contain these components, but the cellulose content of the total mass is greater than 85% by mass.

[0009] In recent years, cellulose nanofibers have been found to have excellent properties, such as high elastic modulus, high strength, low coefficient of linear expansion, and gas barrier properties. In addition, they are lighter than glass fibers, carbon fibers, inorganic fillers, etc.; therefore, research and development of these materials is being conducted with a view to their various uses, such as as a resin reinforcing material, paint additive, film, and thickener.

[0010] Methods for producing cellulose nanofibers include mechanical fiber defibration using a high-pressure dispersion device or grinder, chemically hydrophilizing the pulp with a cationic agent and then mechanically fiberizing it easily using a kneader, and partially oxidizing it using a TEMPO catalyst or the like to make it easier to chemically fiberize.

[0011] Meanwhile, cellulose nanofibers are rarely used alone, and are often used in combination with organic components or organic solvents, but cellulose has a strong hydrophilicity due to the large number of hydroxyl groups on the glucose molecules, and the smaller the diameter of the fiber it is defibrated to, the more likely it is to aggregate due to hydrogen bonds between the hydroxyl groups, and it has the disadvantage of lacking affinity with hydrophobic organic matter. In other words, although it exists stably in water, it is difficult to compound (especially melt-knead) with hydrophobic polymers or hydrolyzable polymers while it contains a lot of water, and when it dries, it aggregates and becomes a foreign substance in the polymer, reducing its properties, making it difficult to demonstrate the properties of cellulose nanofibers in the polymer.

[0012] Methods for hydrophobizing cellulose nanofibers have also been investigated, but most of these involve chemically replacing the hydroxyl groups of cellulose nanofibers with hydrophobic groups. In these cases, problems remain, such as high costs and the inability to completely suppress aggregation due to hydrogen bonds, since only a portion of the hydroxyl groups are replaced. In addition, the more hydrophobized the nanofibers are, the bulkier the substituents become, increasing their mass ratio to cellulose and tending to impair strength.

[0013] These issues are similar to those faced by ordinary cellulose fibers, but are particularly pronounced in the case of cellulose nanofibers, which have a large number of hydroxyl groups exposed on their surface relative to their mass.

[0014] Therefore, an object of the present invention is to provide a biomass resin composition that has excellent transparency, strength, and heat resistance without the addition of a non-biomass filler. [Means for solving the problem]

[0015] As a result of intensive research in view of the above object, the present inventors have found that by including a biomass resin and a hydroxyalkyl (alkyl) cellulose compound, a biomass resin composition having excellent transparency, strength, and heat resistance can be obtained without adding a non-biomass filler. Furthermore, they have found that even when cellulose nanofibers are included in this biomass resin composition, strength can be maintained, contrary to the above-mentioned problem. Then, after further research, they have completed the present invention. That is, the present invention includes the following configurations.

[0016] Item 1. A biomass resin composition containing a biomass resin and a hydroxyalkyl (alkyl) cellulose compound.

[0017] Item 2. The biomass resin composition according to Item 1, wherein the hydroxyalkyl (alkyl) cellulose compound is at least one selected from the group consisting of hydroxypropyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl ethyl cellulose.

[0018] Item 3. The biomass resin composition according to Item 1 or 2, wherein the hydroxyalkyl(alkyl)cellulose compound has a weight average molecular weight of 5,000 to 5,000,000.

[0019] Item 4. The biomass resin composition according to any one of Items 1 to 3, wherein 100 mL of an aqueous solution obtained by adding water to 2 g of the hydroxyalkyl(alkyl)cellulose compound has a viscosity of 2 to 6000 mPa·s.

[0020] Item 5. The biomass resin composition according to any one of Items 1 to 4, wherein the content of the hydroxyalkyl(alkyl)cellulose compound is 2 to 50 mass%, based on 100 mass% of the total amount of the biomass resin composition.

[0021] Item 6. The biomass resin is at least one selected from the group consisting of polylactic acid, polyglycolic acid, polyhydroxybutyrate, polybutylene succinate, polyethylene succinate, polyamide 4, polyamide 11, polyethylene, polypropylene, and copolymers thereof. The biomass resin composition according to any one of items 1 to 5.

[0022] Item 7. The biomass resin composition according to any one of Items 1 to 6, wherein the content of the biomass resin is 20 to 97% by mass, with the total amount of the biomass resin composition being 100% by mass.

[0023] Item 8. The biomass resin composition according to any one of Items 1 to 7, wherein a biomass ratio is 99% by mass or more, with the total amount of the biomass resin composition being 100% by mass.

[0024] Item 9. The biomass resin composition according to any one of Items 1 to 8, further comprising cellulose nanofibers.

[0025] Item 10. The biomass resin composition according to Item 9, wherein the cellulose nanofibers have an average diameter of 3 to 1000 nm.

[0026] Item 11. The biomass resin composition according to Item 9 or 10, wherein the content of the cellulose nanofibers is 1 to 30 mass%, based on 100 mass% of the total amount of the biomass resin composition.

[0027] Item 12. A method for producing a biomass resin composition according to any one of items 1 to 11, (A1) A step of kneading the biomass resin and the hydroxyalkyl (alkyl) cellulose compound A manufacturing method comprising:

[0028] Item 13. A method for producing a biomass resin composition according to any one of items 9 to 11, (B1) mixing the hydroxyalkyl(alkyl)cellulose compound and the cellulose nanofibers in the presence of a polar solvent; and (B2) A step of kneading the mixture obtained in step (B1) and the biomass resin. A manufacturing method comprising:

[0029] Item 14. The production method according to Item 13, further comprising a step of defibrating the cellulose nanofibers in the presence of the hydroxyalkyl (alkyl) cellulose compound using the mixture obtained in step (B1) prior to step (B2). Effect of the Invention

[0030] According to the present invention, it is possible to provide a biomass resin composition that is excellent in transparency, strength, and heat resistance without adding a non-biomass filler. [Brief description of the drawings]

[0031] [Figure 1] Photographs showing the state (with one side fixed) of test pieces of Examples 1 to 3 and Comparative Example 1 before heating in Experimental Example 1. From the left, the samples are Comparative Example 1, Example 3, Example 3, Example 2, and Example 1 (there are two samples of Example 3). [Diagram 2] 1 is a photograph showing the state (deformation amount) of a test piece after heating in Experimental Example 1. From the left, Comparative Example 1, Example 1, Example 2, and Example 3. [Diagram 3] 1 is an external photograph showing transparency when sheets were produced by hot pressing the resin compositions of Examples 5, 6 and 7 in Experimental Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] In this specification, the term "containing" is a concept that encompasses all of "comprise," "consist essentially of," and "consist only of."

[0033] In this specification, when a numerical range is expressed as A to B, it means A or more and B or less.

[0034] As used herein, the term "hydroxyalkyl (alkyl) cellulose compound" encompasses both hydroxyalkyl cellulose compounds and hydroxyalkyl alkyl cellulose compounds.

[0035] The biomass resin composition of the present invention contains a biomass resin and a hydroxyalkyl (alkyl) cellulose compound.

[0036] 1.Biomass resin The biomass resin can be any resin derived from biomass, and examples thereof include polylactic acid, polyglycolic acid, polyhydroxybutyrate, polybutylene succinate, polyethylene succinate, polyamide 4, polyamide 11, biomass polyethylene, biomass polypropylene, and copolymers thereof. The biomass resin may be a resin obtained by chemically modifying a biomass material as a main component, such as cellulose acetate. These biomass resins may be used alone or in combination of two or more kinds. The biomass resin may be a biodegradable biomass resin or a non-biodegradable biomass resin. Among them, from the viewpoints of transparency, strength, and heat resistance, biodegradable biomass resin is preferred, and polylactic acid is more preferred.

[0037] Polylactic acid is a polymer or copolymer of lactic acid monomers, dimers, oligomers, etc. As the polylactic acid, a commercially available product or one polymerized by a conventional method can be used, and there is no particular limitation on the polymerization method.

[0038] Examples of polylactic acid include poly-L-lactic acid (polylactic acid having L-lactic acid as the main repeating unit) and poly-D-lactic acid (polylactic acid having D-lactic acid as the main repeating unit), and either can be used. A typical polylactic acid is a copolymer of L-lactic acid and D-lactic acid, and is often mainly composed of L-lactic acid structure. In this case, it is preferable that the L-lactic acid structure is more abundant and the D-lactic acid structure is less abundant. From the viewpoints of transparency, strength, heat resistance, etc., the ratio of the D-lactic acid structure to the total lactic acid structure is preferably 0 to 3 mol%, more preferably 0 to 2 mol%, and even more preferably 0 to 1 mol%. In addition, a stereocomplex, which is a mixture of L-lactic acid polymer and D-lactic acid polymer, is also preferable from the viewpoint of high heat resistance of the resin.

[0039] 2. Hydroxyalkyl(alkyl)cellulose compounds The hydroxyalkyl (alkyl) cellulose compound used in the present invention is not particularly limited, and examples thereof include hydroxypropyl cellulose (HPC) in which all or a portion of the hydroxyl groups of cellulose are substituted with 2-hydroxy n-propyl groups; hydroxyethyl cellulose (HEC) in which all or a portion of the hydroxyl groups of cellulose are substituted with 2-hydroxyethyl groups; hydroxypropyl methylcellulose (HPMC) in which all or a portion of the hydroxyl groups of cellulose are substituted with methyl groups and 2-hydroxy n-propyl groups, and thus has at least one methyl group and one 2-hydroxy n-propyl group; and hydroxypropyl ethyl cellulose (HPEC) in which all or a portion of the hydroxyl groups of cellulose are substituted with methyl groups and 2-hydroxyethyl groups, and thus has at least one methyl group and one 2-hydroxyethyl group. Collectively, these refer to a homopolymer of glucose in which all or a part of the hydroxyl groups have been substituted with at least one type of group, such as a 2-hydroxy n-propyl group, a 2-hydroxyethyl group, a methyl group, etc., or a copolymer of unsubstituted glucose and glucose in which all or a part of the hydroxyl groups have been substituted with at least one type of group, such as a 2-hydroxy n-propyl group, a 2-hydroxyethyl group, a methyl group, etc.

[0040] The above-mentioned hydroxyalkyl (alkyl) cellulose compounds can be used alone or in combination of two or more kinds. In addition, these hydroxyalkyl (alkyl) cellulose compounds can be appropriately selected according to the required properties.

[0041] However, in the case of methylcellulose, in which all or part of the hydroxyl groups of cellulose have been replaced with methyl groups, discoloration occurs and strength becomes insufficient.

[0042] Among them, when strength and heat resistance are important, hydroxypropyl cellulose is preferred, and when transparency is important, hydroxyethyl cellulose is preferred.

[0043] In general, all hydroxyl groups of a hydroxyalkyl (alkyl) cellulose compound are often substituted, and in this case, the compound is water-soluble. However, from the viewpoint of transparency, strength, and heat resistance, it is preferable to use a hydroxyalkyl (alkyl) cellulose compound in which the number of hydroxyl groups substituted is small (i.e., the number of hydroxyl groups is large), which is easily swollen in water and has low water solubility. From this viewpoint, the molar substitution degree (average number of hydroxyl groups substituted per glucose) of the hydroxyalkyl (alkyl) cellulose compound is preferably 0.10 to 1.00, more preferably 0.15 to 0.50. For example, L-HPC manufactured by Shin-Etsu Chemical Co., Ltd., which is a low-substituted hydroxypropyl cellulose, has a molar substitution degree of about 0.24 to 0.42 (the ratio of hydroxypropoxy groups is 8 to 14 mol%), and is a hydroxyalkyl (alkyl) cellulose compound which is easily swollen in water and has low water solubility. The molar substitution degree of the above-mentioned hydroxyalkyl (alkyl) cellulose compound is: 1 Measured by H-NMR.

[0044] The weight average molecular weight of the hydroxyalkyl (alkyl) cellulose compound can be appropriately selected according to the physical properties and production needs. In particular, the higher the weight average molecular weight, the easier it is to improve the strength and heat resistance of the biomass resin composition of the present invention obtained. On the other hand, the lower the weight average molecular weight, the easier it is to handle when mixed with cellulose nanofibers described later, and the easier it is to blend the hydroxyalkyl (alkyl) cellulose compound at a higher concentration because it is less likely to become highly viscous, and as a result, the strength and heat resistance are also easier to improve. For this reason, the weight average molecular weight of the hydroxyalkyl (alkyl) cellulose compound is preferably high when the cellulose nanofibers described later are not included, but when the cellulose nanofibers described later are included, it is preferable to appropriately select the weight average molecular weight according to the required characteristics such as handleability, transparency, strength, and heat resistance. From this viewpoint, the weight average molecular weight of the hydroxyalkyl (alkyl) cellulose compound is preferably 5000 to 5,000,000 when the cellulose nanofibers described later are not included, more preferably 100,000 to 5,000,000, and even more preferably 300,000 to 5,000,000. Furthermore, when the cellulose nanofiber described below is contained, the molecular weight of the hydroxyalkyl (alkyl) cellulose compound is preferably 5,000 to 5,000,000, more preferably 100,000 to 4,000,000, and even more preferably 500,000 to 1,000,000. The molecular weight of the hydroxyalkyl (alkyl) cellulose compound is measured by the GPS method.

[0045] The viscosity of the hydroxyalkyl (alkyl) cellulose compound can be appropriately selected according to the physical properties and manufacturing needs. In particular, the higher the viscosity, the easier it is to improve the strength and heat resistance of the biomass resin composition of the present invention obtained. On the other hand, the lower the viscosity, the easier it is to handle when mixed with cellulose nanofibers described below, and since it is less likely to become highly viscous, it is easier to mix the hydroxyalkyl (alkyl) cellulose compound at a higher concentration, and as a result, it is easier to improve the strength and heat resistance. For this reason, the viscosity of a 2% by mass aqueous solution of the hydroxyalkyl (alkyl) cellulose compound is preferably high when the cellulose nanofibers described below are not included, but when the cellulose nanofibers described below are included, it is preferable to appropriately select the viscosity according to the required characteristics such as handleability, transparency, strength, and heat resistance. From this viewpoint, the viscosity of a 2% by mass aqueous solution is preferably 2 to 10,000 mPa·s, more preferably 6 to 8,000 mPa·s, and even more preferably 10 to 6,000 mPa·s. The viscosity of a 2% by mass aqueous solution of the hydroxyalkyl (alkyl) cellulose compound described above is measured using a B-type viscometer.

[0046] 3. Cellulose nanofiber The biomass resin composition of the present invention can improve strength and heat resistance by containing the above-mentioned biomass resin and a hydroxyalkyl (alkyl) cellulose compound. The biomass resin composition of the present invention can also contain cellulose nanofibers from the viewpoint of improving the elastic modulus, strength, and heat resistance.

[0047] As mentioned above, cellulose nanofibers have a strong hydrophilicity due to the large number of hydroxyl groups on the glucose molecules. As the cellulose nanofiber is defibrated to a finer diameter, it tends to aggregate more strongly due to hydrogen bonds between the hydroxyl groups, and it lacks affinity for hydrophobic organic matter.

[0048] For this reason, in the absence of the above-mentioned hydroxyalkyl (alkyl) cellulose compounds, they exist stably in water, but if they remain in a state containing a large amount of water, they are difficult to compound (especially by melt-kneading) with hydrophobic biomass resin, and when they dry, they aggregate and become foreign matter in the biomass resin, which is one of the causes of reduced strength.

[0049] However, in the present invention, when cellulose nanofibers are incorporated in the presence of the above-mentioned hydroxyalkyl (alkyl) cellulose compound, the affinity with the hydrophobic biomass resin is improved even in a state containing a large amount of water in which the cellulose nanofibers are stable, making it easier to prevent aggregation even when dried, to suppress discoloration, to maintain transparency, and to maintain strength and heat resistance.

[0050] The cellulose nanofibers may be any of the known cellulose nanofibers, and are not particularly limited. In addition, any of plant-derived cellulose nanofibers, animal-derived cellulose nanofibers, and bacterial-derived cellulose nanofibers may be used. These cellulose nanofibers may be used alone or in combination of two or more kinds.

[0051] Examples of plant-derived cellulose nanofibers include cellulose nanofibers derived from broad-leaved trees (eucalyptus, poplar, etc.), cellulose nanofibers derived from conifers (pine, fir, cedar, cypress, etc.), cellulose nanofibers derived from herbaceous plants (straw, bagasse, reed, kenaf, abaca, sisal, etc.), and seed hair fibers (cotton, etc.). The raw pulp may be mechanical pulp obtained by mechanically treating wood chips, chemical pulp obtained by chemically removing non-cellulose components from wood chips, or dissolving pulp obtained by further removing non-cellulose components and refining.

[0052] In addition, cellulose nanofibers derived from animals such as sea squirts, and cellulose nanofibers derived from bacteria such as nata de coco can also be used.

[0053] The above cellulose nanofibers do not necessarily have to be composed of pure cellulose components, but may contain non-cellulose components in addition to the main component cellulose. Of course, the cellulose nanofibers may be composed of pure cellulose components.

[0054] The main non-cellulose components associated with the cellulose nanofibers are not particularly limited and can be appropriately selected depending on the application of the biomass resin composition. Examples include hemicellulose and lignin. The more hemicellulose, the easier it is to defibrate the cellulose nanofibers during production, but the strength and heat resistance of the resulting biomass resin composition are likely to decrease. On the other hand, the more lignin, the more difficult it is to defibrate the cellulose nanofibers during production, but the strength and heat resistance of the biomass resin composition are likely to improve.

[0055] The ratio of the pure cellulose component in the cellulose nanofibers can also be appropriately set depending on the application of the biomass resin composition of the present invention. For example, from the viewpoint that the biomass resin composition of the present invention reinforces the biomass resin, the ratio of the pure cellulose component is preferably 70 to 100 mass%, more preferably 80 to 100 mass%, based on the total amount of the cellulose nanofibers being 100 mass%, in order to effectively utilize the strength characteristics of the cellulose component. In this specification, the cellulose ratio means the ratio of the pure cellulose component in which β-glucose molecules are linearly polymerized through glycosidic bonds.

[0056] The degree of polymerization of the cellulose contained in the cellulose nanofibers can also be appropriately set depending on the application of the biomass resin composition of the present invention. The lower the degree of polymerization of the cellulose contained in the cellulose nanofibers, the easier the cellulose nanofibers tend to be defibrated. On the other hand, the higher the degree of polymerization of the cellulose contained in the cellulose nanofibers, the easier it is to improve the strength and heat resistance. From this perspective, the degree of polymerization of the cellulose contained in the cellulose nanofibers is preferably 500 to 100,000, and more preferably 600 to 80,000.

[0057] Regarding the crystallinity of the cellulose component contained in the cellulose nanofiber, the lower the crystallinity, the easier it is to defibrate, but the higher the crystallinity, the easier it is to improve strength and heat resistance. From this perspective, the crystallinity of the cellulose component contained in the cellulose nanofiber is preferably 60 to 99%, and more preferably 70 to 98% or more. The crystal structure of cellulose can be type I, type II, type III, or type IV, and among these, from the perspective of reinforcing biomass resin, cellulose with type I crystal structure, which has high strength and heat resistance, is preferred.

[0058] Cellulose fibers contained in pulp usually have a diameter of 10 to 100 μm, but from the viewpoints of preventing aggregation, transparency, strength, heat resistance, etc., the cellulose nanofibers used in the present invention are preferably further refined, and specifically, the average diameter is preferably 3 to 1000 nm, more preferably 4 to 100 nm. The average diameter of the cellulose nanofibers is the median diameter obtained by SEM observation of 50 or more randomly selected cellulose nanofibers.

[0059] Generally, when cellulose nanofibers are ideally refined without impairing the length, crystallinity, and degree of polymerization, and ideally dispersed, the strength and heat resistance of the resulting biomass resin composition are likely to be improved. However, in reality, it is assumed that the thinner and longer the cellulose nanofibers are, the more likely they are to aggregate, making it difficult to improve the strength of the biomass resin composition. In addition, since the length, crystallinity, and degree of polymerization of the nanofibers may decrease when the cellulose nanofibers are refined to nano size, it is preferable to appropriately set the appropriate degree of refinement depending on the purpose and the means of refinement. In addition, according to the present invention, since the cellulose nanofibers coexist with the above-mentioned hydroxyalkyl (alkyl) cellulose compound, they can be defibrated while being less likely to aggregate, and therefore even if they are refined excessively, they are less likely to aggregate, and transparency, strength, and heat resistance are easily improved.

[0060] The method of refining cellulose nanofibers can be widely adopted from known methods, and is not particularly limited. Specifically, it may be a physical method such as a high-pressure homogenizer method, an underwater collision method, a grinder method, a ball mill method, or a biaxial kneading method, or it may be a chemical method using a TEMPO catalyst, phosphoric acid, a dibasic acid, sulfuric acid, hydrochloric acid, or the like. Usually, the average diameter of cellulose nanofibers is likely to be 10 to 1000 nm by physical methods, but it is easy to obtain cellulose nanofibers with an even thinner average diameter of 3 to 10 nm by chemical methods. On the other hand, the smaller the diameter and the larger the aspect ratio, the higher the physical properties such as strength of the obtained biomass resin composition can be expected, but the viscosity may increase, the production efficiency may decrease, or the high strength may be difficult to improve due to aggregation. Therefore, it is preferable to appropriately set the appropriate degree of refining depending on the purpose and the means of refining. According to the present invention, since the cellulose nanofiber coexists with the above-mentioned hydroxyalkyl (alkyl) cellulose compound, it is possible to defibrate the cellulose nanofiber while making it difficult to aggregate, and therefore it is difficult to aggregate even if it is excessively refined, and it is easy to improve transparency, strength, and heat resistance.

[0061] 4. Biomass resin composition The biomass resin composition of the present invention contains a biomass resin and a hydroxyalkyl (alkyl) cellulose compound, and, as necessary, cellulose nanofibers.

[0062] In the biomass resin composition of the present invention, the content of the biomass resin is preferably 20 to 97 mass%, more preferably 35 to 94 mass%, and even more preferably 50 to 91 mass%, based on 100 mass% of the total amount of the biomass resin composition of the present invention, from the viewpoints of transparency, strength, heat resistance, prevention of aggregation, etc.

[0063] In the biomass resin composition of the present invention, the content of the hydroxyalkyl(alkyl)cellulose compound is preferably 2 to 50 mass%, more preferably 3 to 40 mass%, and even more preferably 4 to 30 mass%, based on 100 mass% of the total amount of the biomass resin composition of the present invention, from the viewpoints of transparency, strength, heat resistance, prevention of aggregation, etc.

[0064] When the biomass resin composition of the present invention contains cellulose nanofibers, the content of the cellulose nanofibers is preferably 1 to 30 mass%, more preferably 3 to 25 mass%, and even more preferably 5 to 20 mass%, based on 100 mass% of the total amount of the biomass resin composition of the present invention, from the viewpoints of transparency, strength, heat resistance, prevention of aggregation, etc.

[0065] The biomass resin composition of the present invention is not limited to the above-mentioned biomass resin and hydroxyalkyl (alkyl) cellulose compound, and, if necessary, cellulose nanofibers, and may also contain various additives.

[0066] Such additives may include, for example, fluorene compounds, which are less likely to impair heat resistance and strength, more likely to suppress aggregation of cellulose nanofibers, and more likely to increase hydrophobicity, thereby more likely to improve dispersibility.

[0067] Examples of such fluorene compounds include 9,9-bis(glycidyloxyphenyl)fluorenes and 9,9-bis(glycidyloxyalkoxyphenyl)fluorenes. Examples of 9,9-bis(glycidyloxyphenyl)fluorenes include 9,9-bis(monoglycidyloxyphenyl)fluorenes such as 9,9-bis(4-glycidyloxyphenyl)fluorene (BPFG) and 9,9-bis(4-glycidyloxy-3-methylphenyl)fluorene (BCFG); 9,9-bis(diglycidyloxyphenyl)fluorenes such as 9,9-bis[3,4-di(glycidyloxy)phenyl]fluorene (biscatecholfluorene tetraglycidyl ether); Examples of the 9,9-bis(glycidyloxyalkoxyphenyl)fluorenes include 9,9-bis(triglycidyloxyphenyl)fluorenes such as 9,9-bis[3,4,5-tri(glycidyloxy)phenyl]fluorene. Examples of the 9,9-bis(glycidyloxyalkoxyphenyl)fluorenes include 9,9-bis(monoglycidyloxyalkoxyphenyl)fluorenes such as 9,9-bis(4-glycidyloxyethoxyphenyl)fluorene (bisphenoxyethanolfluorene diglycidyl ether) (BPEFG) and 9,9-bis(4-glycidyloxyethoxy-3-methylphenyl)fluorene (BCEFG); and the corresponding 9,9-bis(di- or tri(glycidyloxyalkoxy)phenyl)fluorenes.

[0068] When the biomass resin composition of the present invention contains a fluorene compound, the content of the fluorene compound is preferably 1 to 30 mass%, more preferably 3 to 25 mass%, and even more preferably 5 to 20 mass%, based on 100 mass% of the total amount of the biomass resin composition of the present invention, from the viewpoints of transparency, strength, heat resistance, prevention of aggregation, etc.

[0069] The method for producing the biomass resin composition of the present invention as described above is not particularly limited, but may be, for example, (A1) A step of kneading a biomass resin and a hydroxyalkyl (alkyl) cellulose compound The manufacturing method can be obtained by the method.

[0070] On the other hand, when cellulose nanofibers are contained in the biomass resin composition of the present invention, from the viewpoint of preventing aggregation, (B1) mixing a hydroxyalkyl(alkyl)cellulose compound and cellulose nanofibers in the presence of a polar solvent; and (B2) A step of kneading the mixture obtained in step (B1) and the biomass resin. It is preferable that the above-mentioned manufacturing method is used.

[0071] When an additive such as a fluorene compound is added to the biomass resin composition of the present invention, it is preferable to add the additive in step (A1) and step (B1).

[0072] The biomass resin, the hydroxyalkyl (alkyl) cellulose compound, the cellulose nanofiber, and the fluorene compound can be those described above. The same applies to the preferred conditions.

[0073] The hydroxyalkyl(alkyl)cellulose compound may be in the form of a powder, or may be in a state wetted with various solvents.

[0074] In step (B1), the method for mixing the hydroxyalkyl(alkyl)cellulose compound and the cellulose nanofibers in the presence of a polar solvent is not particularly limited. Specifically, the hydroxyalkyl(alkyl)cellulose compound, the cellulose nanofibers, and the polar solvent can be mixed by a conventional method.

[0075] The polar solvent that can be used in this case is not particularly limited, and either water or a polar organic solvent can be used.

[0076] The polar organic solvent preferably has a high affinity with the hydroxyalkyl (alkyl) cellulose compound and the cellulose nanofiber, and if necessary, the fluorene compound. From the viewpoint of affinity with the hydroxyalkyl (alkyl) cellulose compound, and if necessary, the cellulose nanofiber and the fluorene compound, the polar organic solvent preferably has an oxyalkylene group, a ketone group, an ester group, a sulfinyl group, or the like.

[0077] As a polar organic solvent satisfying such conditions, it is preferable to include an oxyethylene group, an oxypropylene group, a cyclic ketone group, a cyclic ester group, a dialkyl sulfoxide group, etc., and a diethylene glycol dialkyl ether compound, a dipropylene glycol dialkyl ether compound, an aliphatic cyclic ketone compound, an alkyl acetate compound, an alkyl propionate compound, an alkyl butyrate compound, etc. are suitable. Diethylene glycol dimethyl ether, dipropylene glycol dimethyl ether, cyclohexanone, cyclopentanone, butyl acetate, pentyl acetate, isopentyl acetate, butyl butyrate, pentyl butyrate, isopentyl butyrate, dimethyl sulfoxide, dimethylacetamide, N-methylpyrrolidinone, dimethyl sulfoxide, etc. are particularly preferable. These polar organic solvents can be used alone or in combination of two or more kinds. However, the polar organic solvent does not need to be limited to these, and it is preferable to select it from the viewpoint of affinity with the hydroxyalkyl (alkyl) cellulose compound and cellulose nanofiber to be used, and, if necessary, with the fluorene compound.

[0078] In step (B1), it is preferable to mix the hydroxyalkyl(alkyl)cellulose compound, cellulose nanofibers, and polar solvent in a conventional manner as described above, and then defibrate the cellulose nanofibers in the presence of the hydroxyalkyl(alkyl)cellulose compound. The defibration method is not particularly limited and can be carried out according to a conventional method.

[0079] In steps (A1) and (B2), the kneading method is not particularly limited and may be dry kneading or melt kneading. In particular, melt kneading is preferred from the viewpoints of productivity, dispersibility, transparency, strength, and heat resistance.

[0080] In step (B2), the polar solvent (water or polar organic solvent) used in step (B1) can be used as is for melt-kneading. However, when water is used, it is preferable to perform melt-kneading under vacuum in order to easily suppress hydrolysis of polylactic acid.

[0081] In addition, when melt kneading is employed, it is preferable that the polar solvent (water or polar organic solvent) used increases the affinity of the biomass resin and the hydroxyalkyl (alkyl) cellulose compound, and, if necessary, the cellulose nanofibers and the fluorene compound during kneading, and then the polar solvent (water or polar organic solvent) is removed. From the viewpoints of particularly excellent workability at this time, particularly resistance to aggregation of the hydroxyalkyl (alkyl) cellulose compound and, if necessary, the cellulose nanofibers, and particularly ease of removal of the organic solvent, the boiling point of the polar organic solvent is preferably 50 to 250°C, more preferably 70 to 230°C.

[0082] In addition, when the biomass resin used is a polyester resin, a polyamide resin, or the like that undergoes hydrolysis or alcoholysis, it is preferable that the polar organic solvent does not have a hydroxyl group so as not to cause unnecessary reactions with the biomass resin. EXAMPLES

[0083] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.

[0084] In the following examples and comparative examples, each component was mixed by melt mixing. Specifically, a biomass resin dried at 80°C for 24 hours and a hydroxyalkyl (alkyl) cellulose compound were melt mixed using a twin-screw extruder (manufactured by Technovel Co., Ltd.; screw diameter 15 mmφ, screw process length L / D = 30) to obtain pellets. The obtained pellets were dried at 80°C for 24 hours, and then molded into dumbbell test pieces with a length of 75 mm, a parallel part width of 5 mm, a parallel part length of 35 mm, and a thickness of 2 mm using an injection molding machine (manufactured by Shinko Selvic Co., Ltd.; C,MOBILE-0813).

[0085] Example 1 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of hydroxypropyl cellulose (HPC-SSL manufactured by Nippon Soda Co., Ltd.; weight average molecular weight 40,000; viscosity of 2-2.9 mPa s when 2 g of the polylactic acid was added to water to make 100 mL of aqueous solution) were mixed in a twin-screw mixer to produce pellets. The resulting pellets were injection molded to obtain a translucent molded product.

[0086] Example 2 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of hydroxypropyl cellulose (HPC-SL manufactured by Nippon Soda Co., Ltd.; weight average molecular weight 100,000; viscosity when 2 g of the material was added to water to make 100 mL of aqueous solution: 3-5.9 mPa s) were mixed in a twin-screw mixer to produce pellets. The resulting pellets were injection molded to obtain a translucent molded product.

[0087] Example 3 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of hydroxypropyl cellulose (HPC-L manufactured by Nippon Soda Co., Ltd.; weight average molecular weight 140,000; viscosity of the aqueous solution when 2 g of the material was added to water to make 100 mL was 6-10 mPa s) were mixed in a twin-screw mixer to produce pellets. The resulting pellets were injection molded to obtain a translucent molded product.

[0088] Example 4 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of hydroxypropyl cellulose (HPC-M manufactured by Nippon Soda Co., Ltd.; weight average molecular weight 700,000; viscosity of 2% by mass aqueous solution 150-400 mPa s) were mixed in a twin-screw mixer to produce pellets. The resulting pellets were injection molded to obtain a translucent molded product.

[0089] Example 5 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of hydroxypropyl cellulose (HPC-H manufactured by Nippon Soda Co., Ltd.; weight average molecular weight 1,000,000; viscosity of the aqueous solution when 2 g of the polylactic acid is added to 100 mL with water is 1,000-4,000 mPa s) were mixed in a twin-screw mixer to produce pellets. The resulting pellets were injection molded to obtain a translucent molded product.

[0090] Example 6 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of hydroxypropyl methylcellulose (60SH-15 manufactured by Shin-Etsu Chemical Co., Ltd.; molar substitution: methoxy group 1.9, hydroxypropoxy group 0.25; viscosity of the aqueous solution when 2 g of the material was added to 100 mL of water was 15 mPa s) were mixed in a twin-screw mixer to produce pellets. The resulting pellets were injection molded to obtain a translucent molded product.

[0091] Example 7 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of hydroxyethyl methylcellulose (SNB-60T manufactured by Shin-Etsu Chemical Co., Ltd.; molar substitution: methoxy group 1.5, hydroxyethoxy group 0.30; viscosity of the aqueous solution when 2 g of the polylactic acid was added to 100 mL of water was 60,000 mPa s) were mixed in a twin-screw mixer to produce pellets. The resulting pellets were injection molded to obtain a translucent molded product.

[0092] Example 8 180 g of polylactic acid (TE-2000, manufactured by Unitika Ltd.) and 20 g of hydroxyethyl cellulose (first-class manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.; viscosity of the aqueous solution when 2 g is added to water to make 100 mL is 200 mPa s) were kneaded in a twin-screw kneader to produce pellets. The resulting pellets were injection molded to obtain a transparent molded product. Since a more transparent molded product was obtained compared to the case of the polylactic acid in Comparative Example 1, it is suggested that polylactic acid and hydroxyethyl cellulose have excellent compatibility.

[0093] Example 9 200 g of pulp (hardwood pulp manufactured by Marubeni Corporation), 100 g of hydroxypropyl cellulose (HPC-SSL manufactured by Nippon Soda Co., Ltd.; weight average molecular weight 40,000; viscosity of the aqueous solution when 2 g of hydroxypropyl cellulose was added to make 100 mL with water was 2-2.9 mPa s) and 9,700 g of water were mixed and the pulp was defibrated using an electric mortar. As a result, a composite dispersion containing cellulose nanofibers (average diameter 50 nm) and hydroxypropyl cellulose was obtained.

[0094] The obtained composite dispersion was dried under reduced pressure at 80°C to obtain a powder containing 66.7% by mass of cellulose nanofibers and 33.3% by mass of hydroxypropyl cellulose.

[0095] 170 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 30 g of the powder obtained above were kneaded in a twin-screw kneader to prepare pellets. The obtained pellets were injection molded to obtain a translucent molded product.

[0096] Example 10 200 g of pulp (hardwood pulp manufactured by Marubeni Corporation), 100 g of hydroxypropyl cellulose (HPC-SSL manufactured by Nippon Soda Co., Ltd.; weight average molecular weight 40,000; viscosity of the aqueous solution when 2 g is added to water to make 100 mL is 2-2.9 mPa s), 100 g of bisphenoxyethanol fluorene glycidyl ether, and 9,600 g of water were mixed and the pulp was defibrated in an electric mill. As a result, a composite dispersion containing cellulose nanofibers (average diameter 50 nm), hydroxypropyl cellulose, and bisphenoxyethanol fluorene glycidyl ether was obtained.

[0097] The obtained composite dispersion was dried under reduced pressure at 80°C to obtain a powder containing 50.0 mass% cellulose nanofibers, 25.0 mass% hydroxypropyl cellulose, and 25.0 mass% bisphenoxyethanol fluorenediglycidyl ether.

[0098] 160 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 40 g of the powder obtained above were kneaded in a twin-screw kneader to prepare pellets. The obtained pellets were injection molded to obtain a translucent molded product.

[0099] Comparative Example 1 200 g of polylactic acid (TE-2000, manufactured by Unitika Ltd.) was kneaded in a twin-screw kneader to produce pellets. The pellets obtained were injection molded to obtain a nearly transparent molded product.

[0100] Comparative Example 2 200 g of pulp (hardwood pulp manufactured by Marubeni Corporation) and 9,800 g of water were mixed and the pulp was defibrated using an electric mill. As a result, a dispersion containing cellulose nanofibers (average diameter 50 nm) was obtained.

[0101] The resulting dispersion was dried under reduced pressure at 80°C to obtain a dried cellulose nanofiber powder.

[0102] 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of the powder obtained above were mixed in a twin-screw mixer to produce pellets. The resulting pellets were injection molded, but the cellulose nanofibers aggregated, resulting in a non-uniform molded product. When dried alone, the cellulose nanofibers are very prone to aggregation and act as foreign matter, suggesting that the strength was reduced compared to Comparative Example 1, which contained only polylactic acid.

[0103] Experimental Example 1 For the molded products (test pieces) obtained in Examples 1 to 3 and Comparative Example 1, one side of the test piece (the upper side in FIG. 1) was fixed and placed in an electric furnace at 80° C. and heated for 11 hours, as shown in FIG. 1. In FIG. 1, the samples are, from the left, Comparative Example 1, Example 3, Example 3, Example 2, and Example 1 (there are two samples of Example 3 in FIG. 1).

[0104] After heating, the deformation amount of the test piece was measured. The results are shown in Table 1 and Figure 2. In Figure 2, the test pieces are, from the left, Comparative Example 1, Example 1, Example 2, and Example 3. It can be seen that the deformation amount is smaller in Examples 1 to 3 than in Comparative Example 1, and that they have excellent heat resistance. Note that, after molding (before heating), Examples 1 to 3 were translucent, and Comparative Example 1 was almost transparent, but crystallization progressed due to heating and they became almost opaque.

[0105] [Table 1]

[0106] Experimental Example 2 The molded products (test pieces) obtained in Examples 5 to 8 and Comparative Example 1 were also measured for the amount of deformation caused by heating with one side fixed, in the same manner as in Experimental Example 1. The results are shown in Table 2. Compared with Comparative Example 1, the amount of deformation was small in Examples 5 to 8, and it can be seen that they are excellent in heat resistance. Note that after molding (before heating), Examples 5 to 7 were translucent, Example 8 was transparent, and Comparative Example 1 was almost transparent, but all of them became almost opaque due to the progress of crystallization caused by heating.

[0107] [Table 2]

[0108] Experimental Example 3 The molded products (test pieces) obtained in Examples 1 to 3 and Comparative Example 1 were first placed on a flat surface in an electric furnace at 80°C and heated for 3 hours, and then, similarly to Experimental Example 1, one side was fixed and placed in an electric furnace at 80°C and heated for 11 hours.

[0109] After heating, the deformation of the test pieces was measured. The results are shown in Table 3. Here again, it can be seen that the deformation is extremely small in Examples 1 to 3 compared to Comparative Example 1, and that the heat resistance is excellent. In particular, in Comparative Example 1, even when the crystallinity was increased by heating in advance on a flat surface (in a state where it was not deformed by gravity), the heat resistance was insufficient. Note that, after molding (before heating), Examples 1 to 3 were translucent, and Comparative Example 1 was almost transparent, but both became almost opaque due to the progress of crystallization caused by heating.

[0110] [Table 3]

[0111] Experimental Example 4 The tensile strength was measured in accordance with JIS K7161-2:2014 at a test speed of 10 mm / min for Examples 5 to 7, 9 to 10, and Comparative Example 2. The results are shown in Table 4.

[0112] [Table 4]

[0113] As a result, compared to Comparative Example 3, in which only cellulose nanofibers were added to polylactic acid, Examples 5 to 7, in which hydroxypropyl cellulose, hydroxypropyl methylcellulose or hydroxyethyl methylcellulose was added to polylactic acid, Example 9, in which hydroxypropyl cellulose and cellulose nanofibers were added to polylactic acid, and Example 10, in which hydroxypropyl cellulose, cellulose nanofibers and bisphenoxyethanol fluorenediglycidyl ether were added to polylactic acid, had higher strength.

[0114] This suggests that by adding a hydroxyalkyl (alkyl) cellulose compound, and, if necessary, cellulose nanofibers, to polylactic acid, a biomass resin, the dispersibility in polylactic acid is higher and the strength is higher than in a molded product made by adding only cellulose nanofibers to polylactic acid, a biomass resin.

[0115] Experimental Example 5 The resin compositions of Examples 5, 6, and 7 were hot-pressed at 190° C. to prepare sheets of about 150 μm, and the transparency was visually observed. The results are shown in FIG. 3 (only dotted lines were added on the photograph to show the position of the film).

[0116] Thus, in all formulations, a nearly transparent sheet was easily obtained, even though polylactic acid and dry powder were kneaded together. The sheet was also nearly transparent in Example 5, which used hydroxypropyl cellulose, which has a higher molecular weight than Examples 1 to 4, and Example 7, which used hydroxyethyl methyl cellulose, which is presumed to have a higher molecular weight, was found to have even higher transparency.

[0117] Comparative Example 3 180 g of polylactic acid (TE-2000, manufactured by Unitika Ltd.) and 20 g of carboxymethylcellulose sodium salt (manufactured by Sigma-Aldrich; weight-average molecular weight: 250,000) were mixed in a twin-screw mixer to produce pellets, but the resin turned an opaque brown and became brittle; a homogeneous resin composition was not obtained.

[0118] Comparative Example 4 180 g of polylactic acid (TE-2000 manufactured by Unitika Ltd.) and 20 g of alginic acid (alginic acid (non-swelling) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed in a twin-screw mixer to produce pellets, but the resin turned an opaque brown color and became brittle, and a homogeneous resin composition was not obtained.

[0119] From the results of Comparative Examples 3 and 4, it can be understood that even polysaccharides containing cellulose derivatives do not necessarily have compatibility with polylactic acid. Therefore, it is suggested that hydroxyalkyl (alkyl) cellulose compounds are specifically highly compatible with polylactic acid.

Claims

1. A biomass resin composition containing a biomass resin, a hydroxyalkyl(alkyl)cellulose compound, and a cellulose nanofiber, wherein the content of the cellulose nanofiber is 1 to 10 mass% with respect to 100 mass% of the total amount of the biomass resin composition.

2. The biomass resin composition according to claim 1, wherein the hydroxyalkyl (alkyl) cellulose compound is at least one selected from the group consisting of hydroxypropyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and hydroxypropyl ethyl cellulose.

3. The biomass resin composition according to claim 1 or 2, wherein the weight average molecular weight of the hydroxyalkyl(alkyl)cellulose compound is 5,000 to 5,000,000.

4. The biomass resin composition according to any one of claims 1 to 3, wherein the hydroxyalkyl (alkyl) cellulose compound has a viscosity of 2 to 6000 mPa·s when 2 g of the compound is added to 100 mL of water.

5. The biomass resin composition according to any one of claims 1 to 4, wherein the content of the hydroxyalkyl (alkyl) cellulose compound is 2 to 50 mass%, based on 100 mass% of the total amount of the biomass resin composition.

6. The biomass resin is at least one selected from the group consisting of polylactic acid, polyglycolic acid, polyhydroxybutyrate, polybutylene succinate, polyethylene succinate, polyamide 4, polyamide 11, polyethylene, polypropylene, and copolymers thereof. The biomass resin composition according to any one of claims 1 to 5.

7. The biomass resin composition according to any one of claims 1 to 6, wherein the biomass resin is polylactic acid.

8. The biomass resin composition according to any one of claims 1 to 7, wherein the content of the biomass resin is 20 to 97% by mass, with the total amount of the biomass resin composition being 100% by mass.

9. The biomass resin composition according to any one of claims 1 to 8, wherein the biomass ratio is 99% by mass or more, with the total amount of the biomass resin composition being 100% by mass.

10. The biomass resin composition according to any one of claims 1 to 9, wherein the cellulose nanofibers have an average diameter of 3 to 1000 nm.

11. A method for producing a biomass resin composition according to any one of claims 1 to 10, (B1) mixing the hydroxyalkyl(alkyl)cellulose compound and the cellulose nanofibers in the presence of a polar solvent; and (B2) A step of kneading the mixture obtained in step (B1) and the biomass resin. A manufacturing method comprising:

12. The method according to claim 11, further comprising, prior to the step (B2), a step of defibrating the cellulose nanofibers in the presence of the hydroxyalkyl(alkyl)cellulose compound using the mixture obtained in the step (B1).

Citation Information

Patent Citations

  • Biodegradable resin composition and antifouling coating compound composition

    JP1995109339A

  • Biodegradable molding, biodegradable material and their production

    JP1998298435A

  • Resin composition and its molding method, and recycling method of resin composition

    JP2002275379A

  • Composition and composite

    JP2011127075A

  • Method for production of cellulose

    JP2011225847A